Pop surrealism : the rise of underground art - Williams, Robert, 1943-; McCormick, Carlo; Reid, Larry, art critic; Anderson, Kirsten (San Francisco, Calif. : Ignition Pub./ Last Gasp, 2004)
A comprehensive survey of pop surrealism art that includes reproductions of more than 150 pieces of work by various artists, including Glenn Barr, Alex Gross, Lisa Petrucci, Shag, and others.
-- Anthony Ausgang -- Glenn Barr -- Tim Biskup -- Kalynn Campbell -- The Clayton brothers -- Joe Coleman -- Camille Rose Garcia -- Alex Gross -- Don Ed Hardy -- Charles Krafft -- Liz McGrath -- Scott Musgrove -- Niagara -- Marion Peck -- Liza Petrucci -- The pizz -- Mark Ryden -- Isabel Samaras -- Todd Schorr -- Shag -- Eric White -- Robert Williams -- XNO.
Includes artist index.
Keywords: Pop art; Surrealism; Arts, Modern -- 20th century